2021
DOI: 10.1029/2020gl090317
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Large‐Scale Response of Hourly Extreme Precipitation to Temperature Variation Over Land

Abstract: Hourly precipitation extremes can intensify with temperature at higher rates than expected from thermodynamic increases explained by the Clausius‐Clapeyron (CC) relationship (∼6.5%/K), but local scaling with surface air temperature is highly variable. Here we use daily dew point temperature, a direct proxy of absolute humidity, to estimate at‐gauge local scaling across six macro‐regions for a global data set of over 7,000 hourly precipitation gauges. We find scaling rates from CC to 2 × CC at more than 60% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 67 publications
(145 reference statements)
4
67
0
Order By: Relevance
“…However, recent work by Ali et al. (2021) has shown consistent scaling at the CC‐rate globally. Using hourly observations of rainfall at 7,000 gauges from the Global Subdaily Rainfall (GSDR) data set (Lewis et al., 2019) across six macroregions, they established a consistent scaling relationship with dewpoint temperature overland at around the CC rate, when averaged over large regions, and at around 2CC locally.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…However, recent work by Ali et al. (2021) has shown consistent scaling at the CC‐rate globally. Using hourly observations of rainfall at 7,000 gauges from the Global Subdaily Rainfall (GSDR) data set (Lewis et al., 2019) across six macroregions, they established a consistent scaling relationship with dewpoint temperature overland at around the CC rate, when averaged over large regions, and at around 2CC locally.…”
Section: Introductionmentioning
confidence: 94%
“…We first estimated the scaling rates using climate reanalysis data for the locations where GSDR data are available. The scaling results using the GSDR data are the same as those presented in Figure 1 in Ali et al (2021) and therefore not as thoroughly discussed here.…”
Section: Evaluating Precipitation Scaling Rates From Climate Reanalysis Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher moisture availability in the atmosphere with warming has been extensively studied and partially explains the observed and simulated rise in short‐duration precipitation extremes, with stronger updrafts also potentially contributing (Giorgi et al., 2016; Held & Soden, 2006; O’Gorman & Schneider, 2009). Many studies have reported increases in precipitation extremes with temperature following the Clausius‐Clapeyron (CC) rate of 7% per K (Ali et al., 2021; Visser et al., 2020). However, higher scaling rates (so called ‘super‐CC scaling’) have been found for hourly precipitation extremes (Ban et al., 2015; Berg et al., 2013; Drobinski et al., 2018; Hodnebrog et al., 2019; Lenderink & van Meijgaard, 2008; van de Vyver et al., 2019).…”
Section: Introductionmentioning
confidence: 99%